A Critical Review on Obstetric Follow-up ofWomen Affected by Systemic Lupus Erythematosus - Danilo Eduardo Abib Pastore; Maria Laura Costa; Mary Angela Parpinelli; Fernanda Garanhani Surita (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective To review the existing recommendations on the prenatal care of women with systemic lupus erythematosus (SLE), based on currently available scientific evidence. Methods An integrative review was performed by two independent researchers, based on the literature available in the MEDLINE (via PubMed), EMBASE and The Cochrane Library databases, using the medical subject headings (MeSH) terms "systemic lupus erythematosus" AND "high-risk pregnancy" OR "prenatal care." Studies published in English between 2007 and 2017 were included; experimental studies and case reports were excluded. In cases of disagreement regarding the inclusion of studies, a third senior researcher was consulted. Forty titles were initially identified; four duplicates were excluded. After reading the abstracts, 7 were further excluded and 29 were selected for a full-text evaluation. Results Systemic lupus erythematosus flares, preeclampsia, gestation loss, preterm birth, fetal growth restriction and neonatal lupus syndromes (mainly congenital heartblock) were the major complications described. The multidisciplinary team should adopt a specific monitoring, with particular therapeutic protocols. There are safe and effective drug options that should be prescribed for a good control of SLE activity. Conclusion Pregnant women with SLE present an increased risk for maternal complications, pregnancy loss and other adverse outcomes. The disease activity may worsen and, thereby, increase the risk of other maternal-fetal complications. Thus, maintaining an adequate control of disease activity and treating flares quickly should be a central goal during prenatal care.